Selling Failed Banks - GRANJA, JOÃO; MATVOS, GREGOR; SERU, AMIT (Journal of Finance, 2017)
ABSTRACT The average FDIC loss from selling a failed bank is 28% of assets. We document that failed banks are predominantly sold to bidders within the same county, with similar assets business lines, when these bidders are well capitalized. Otherwise, they are acquired by less similar banks located further away. We interpret these facts within a model of auctions with budget constraints, in which poor capitalization of some potential acquirers drives a wedge between their willingness and ability to pay for failed banks. We document that this wedge drives misallocation, and partially explains the FDIC losses from failed bank sales.